The writing on the wall: The theme of suicide and the compassionate look in the youth tv-show Rådebank - Anders Lysne, (Nordlit, 2024)
This article analyzes the theme of suicide in NRK's successful youth drama Rod Knock (Rådebank). Departing from a genre perspective on youth drama conventions within Norwegian and Nordic public service broadcasting drama, the article analyzes how the series constructs a compassionate gaze that seeks both to recognize the impossibility of understanding the act of suicide and to show conditions for actions that may contribute to survival.
Keywords: Rådebank; suicide; NRK; youth television; melodrama